PEMODELAN DAN IMPLEMENTASI DESAIN RESPONSIVE WEBSITE SEBAGAI STANDAR INTERFACE PADA MOBILE - Anugerah Bagus Wijaya; Irfan Santiko (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The development of digital technology in this period is very high. The need for consumption of information is so strong that it causes the growth of devices or media to obtain information varies. From the start of print media to electronic media, it is also increasingly prevalent. From observing the development of electronic media, various kinds of devices or can be called